Endogenous exchange rate passthrough when nominal prices are set in advance - Michael B. Devereux; Charles Engel; Peter E. Storgaard (Danmarks Nationalbank, 2002)
This paper develops a model of endogenous exchange rate pass-through within an open economy macroeconomic framework, where both pass-through and the exchange rate are simultaneously determined, and interact with one another. Pass-through is endogenous because firms choose the currency in which they set their export prices. There is a unique equilibrium rate of pass-through under the condition that exchange rate volatility rises as the degree of pass-through falls. We show that the relationship between exchange rate volatility and economic structure may be substantially affected by the presence of endogenous pass-through. Our key results show that pass-through is related to the relative stability of monetary policy. Countries with relatively low volatility of money growth will have relatively low rates of exchange rate pass-through, while countries with relatively high volatility of money growth will have relatively high pass-through rates.
Keywords: 330; Exchange Rate Pass-Through; Ökonometrisches Makromodell; Offene Volkswirtschaft; Theorie